El derecho humano al agua potable en la jurisprudencia del Tribunal Constitucional - Díaz Muñoz, Oscar (Revista de Derecho, 2020)
In Peruvian legal order, the right to potable water has been recognized as a fundamental right, when considering that water is the main natural resource for being essential to life and health. Nonetheless, discussion is kept as to whether it could be regarded as an autonomous right, and whether its acknowledgement must be supported in the clause of not listed rights or in international instruments ratified by Peru. The present article deals with such issues, as well as the analysis and essential content of this right, taking the Peruvian Constitutional court’s jurisprudence as reference.
Keywords: fundamental rigth to potable water; autonomous fundamental rights; acknowledgement of rights; clause of not listed rights; international instruments